Using XPS to determine solute solubility in room temperature ionic liquids. - Silvester, D; Broder, T; Aldous, L; Hardacre, C; Crossley, A; Compton, R (2007)
X-Ray Photoelectron Spectroscopy (XPS) was used to quantify the amount of bromide ions present in two samples of [C(4)mpyrr]Br dissolved in the room temperature ionic liquid (RTIL) [C(4)mpyrr][N(Tf)2]. One sample was of a known concentration (0.436 Br atom%); the other was a saturated solution. The results obtained from quantitative XPS analysis indicated that the saturated sample had a concentration, or solubility, of 0.90 Br atom% (746 mM) at 298 K, which was then independently confirmed by potential-step chronoamperometry of the same solution.